Development of carrot-calamansi nectar - Lao, Lormie Paguntalan (1997.)
Three different ratios of carrot : calamansi (A- 70:30, B- 60:40, C- 50:50) were used in the determination of the most acceptable formulation of carrot-calamansi nectar.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Nectar; Carrots; Calamansi